Theoretical and Methodological Foundations of Motivation as a Basis to Make Foreign Language Teaching Effective - Natalia Menshagina (Proceedings of AICS - Social Sciences, 2018)
Acknowledging that English is the world global language of science and intercultural communication, the problem of studying it is very acute today. However, not all the students are motivated enough to gain knowledge while they do not realize the importance of English. Thus the purpose of this research is to introduce the concept of “motivational maintenance” we work at. To clarify, it is the sequence of teacher's actions together with the curriculum itself aimed at creating a stable motivation for studying the language. Creating a curriculum is not enough, yet based on the "motivational maintenance", it will provide a deep inside into the subject and consequently lead to better results. "Why do I have to be proficient in English if my major is mathematics?" is a fundamental question each student should have an answer. The aim of foreign language teaching is to bring up a student as a competent and proficient language user. The paper provides methodical examples of how to use special educational techniques or tricks to make students be interested in the subject.  Motivation is the key concept in a process of teaching and learning that should not be underestimated. We are sure that to make students proficient a “motivational maintenance” has to be applied in a language-teaching context.Keywords:foreign language teaching, English as a foreign language, motivation, language proficiency.